PENERAPAN PRINSIP SIX SIGMA DALAM MEMBANGUN MANAJEMEN MUTU PENDIDIKAN ISLAM - Rosi Nuresa; Erlyta Mila Adriasty Khosi'in; Abrar Rizqa Febriyani (STAI Ma'had Aly Al-Hikam Malang, 2022)
AbstractThis article focuses on conducting a study on the application of six sigma in building quality management of Islamic education. This article examines the literature on six sigma which is usually applied to the business world and adapts it to the quality management of Islamic education. The authors use are applying the DMAIC methodology (define, measure, analyze, improve, control). The results of the discussion about six sigma there are two forms of application in education quality management. 1) implementation of six sigma in improving the quality of education. Elements that are directly related to the education process in schools are school supervisors, principals, and teachers. From these elements are able to apply six sigma in the process of improving the quality of education, able to overcome or reduce existing problems. 2) the application of six sigma in improving the organization in educational institutions. a) schools carry out designs, b) schools produce graduates who are able to master various cognitive fields, c) schools are able to design a good curriculum, d) schools are able to carry out the learning process in accordance with the curriculum, e) schools determine fair assessments according to the assessment instrument, f) schools have qualifications for competence and education personnel, g) are able to form RKS and RKAS.Keywords: six sigma; Quality management; Islamic education